Application of Convolutional Neural Networks to Spoken Words Evaluation Based on Lip Movements without Accompanying Sound Signal - Perić, Dušan; Bogdanoski, Mitko; Maček, Nemanja (Journal of Computer and Forensic Sciences, 2023)
This paper proposes an approach to evaluate spoken words based on lip movements without accompanying sound signals using convolutional neural networks. The main goal of this research is to prove the efficiency of neural networks in the field, where all data is received from an array of images. The modeling and the hypotheses are validated based on the results obtained for a specific case study. Our study reports on speech recognition from only a sequence of images provided, where all crucial data and features are extracted, processed, and used in a model to create artificial consciousness.
Keywords: machine learning; convolutional neural networks; lip reading